To selection problem of design characteristics of experimental stand - V. I. Trushlyakov; I. Yu. Lesnyak; V. A. Urbansky (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The analysis is done on the state of experimental studies of liquid evaporation in a closed tank in Russia and abroad. On the basis of the theory of similarity including geometric similarity, Reynolds, Nusselt, Prandtl criteria, as well as the real conditions of the evaporation system, the design parameters of the experimental stand (ES) are determined. Using the ANSYS Fluent software package the ES design parameters are refined on the basis of modeling the liquid evaporation process in closed tank. The structure and the scheme of functioning of ES is developed